2015
DOI: 10.4012/dmj.2015-099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resin coating on bond strength of self-adhesive resin cements to dentin

Abstract: This study evaluated the effect of resin coating (COA) on dentin bond strength (BS) of five resin cements (RC). Ten groups were tested, according to RC and COA combinations. RCs were applied onto prepolymerized resin discs, which were bonded to dentin surfaces. Teeth were stored in water for 24 h, subjected to 5,000 thermocycles and sectioned to obtain beams, which were tested in tension. The COA increased the BS for Panavia F2.0, RelyX Unicem, and RelyX Unicem 2, whereas no changes in BS were observed for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
10
0
5
Order By: Relevance
“… Rocca et al 2015 141 Review - - IDS is a crucial step of the indirect restoration fabrication procedure. Giannini et al 2015 74 In vitro Bond strength, Cement type Evaluated the effect of IDS (Clearfil SE Bond + Clearfil Majesty Flow) on the dentin bond strength of five resin cements (RelyX Unicem, RelyX Unicem 2, Clearfil SA Cement, G-Cem, Panavia F2.0). The increase in bond strength was dependent upon the resin cement type.…”
Section: Resultsmentioning
confidence: 99%
“… Rocca et al 2015 141 Review - - IDS is a crucial step of the indirect restoration fabrication procedure. Giannini et al 2015 74 In vitro Bond strength, Cement type Evaluated the effect of IDS (Clearfil SE Bond + Clearfil Majesty Flow) on the dentin bond strength of five resin cements (RelyX Unicem, RelyX Unicem 2, Clearfil SA Cement, G-Cem, Panavia F2.0). The increase in bond strength was dependent upon the resin cement type.…”
Section: Resultsmentioning
confidence: 99%
“…In the resin-coating technique, the dentin and enamel surfaces that are exposed after cavity preparation are coated with a thin film of a coating material or a dentin bonding system combined with a flowable composite resin 1) . Several studies have demonstrated that the resin-coating technique protects the dentin and pulp [2][3][4] through the formation of a hybrid layer, improving the resin cement-dentin bonding in an indirect restoration procedure [5][6][7][8][9] and reducing the pain caused by external physical stimuli as it seals the dentinal tubules [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…It also facilitates the removal of temporary bonding material adhering to the side of the abutment tooth. The resin-coating technique is also effective for self-adhesive cement, which has become more widely used in recent years 39) . In Japan, where society is aging rapidly, the problem of root caries needs to be addressed; the resin-coating technique may be useful for this purpose in clinical applications.…”
Section: Resultsmentioning
confidence: 99%